Time, temporality, and history in process organization studies - Reinecke, Juliane; Suddaby, Roy; Langley, Ann ca. 20. Jh; Tsukas, Charidēmos K. 1961- (Oxford University Press, 2020)
"Time, timing, and temporality are inherently important to organizational process studies, yet time remains an under-theorized construct that has struggled to move much beyond chronological conceptions of "clock" time. Missing from this linear view are ongoing debates about objectivity versus subjectivity in the experience of time, linear versus alternative structures of time, or an appreciation of collective or culturally determined inferences of temporality. This is critical as our understanding of time and temporality can shape how we view and relate to organizational phenomena, either as unfolding processes or stable objects.History is equally important. While we have an intuitive sense of history as a process, organizational theorists have struggled to move beyond two limited conceptualizations: history as a constraint on organization's capacity for change, or history as a unique source of competitive advantage. Both approaches suffer from the restrictive view of history as an objective set of "brute facts" that are exterior to the individuals, organizations, and collectives that experience them. Yet management theory is acquiring an awareness of time, history, and memory as critical elements in processes of organizing. This volume draws together emerging strands of interest in adopting a more nuanced orientation toward time, temporality, and history to better understand the temporal aspects of organizational processes.
Keywords: Operations Research; Time management; Organizational behavior; Aufsatzsammlung